1993
DOI: 10.1162/jocn.1993.5.2.235
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology of Sensory and Language Processing in Language-Impaired Children

Abstract: Clinical, behavioral, and neurophysiological studies of developmental language impairment (LI), including reading disability (RD), have variously emphasized different factors that may contribute to this disorder. These include abnormal sensory processing within both the auditory and visual modalities and deficits in linguistic skills and in general cognitive abilities. In this study we employed the event-related brain potential (ERP) technique in a series of studies to probe and compare Merent aspects of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
153
8
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(184 citation statements)
references
References 61 publications
(65 reference statements)
19
153
8
4
Order By: Relevance
“…Second, increased neural synchrony, which has been linked to perceptual learning (Merzenich et al, 1999), can be demonstrated through changes in evoked potentials. Third, auditory evoked potentials have been shown to reflect perception in normal and impaired children (Neville et al, 1993;Ponton et al, 1996;Tonnquist-Uhlen, 1996;Jordan et al, 1997;Cunningham et al, 2000Cunningham et al, , 2001. Fourth, deficits in the encoding of speech signals in quiet have been demonstrated at the auditory brainstem level and in both quiet and noise at cortical levels in learning-impaired children (Kraus et al, 1996;Schulte-Koerne et al, 1998;Cunningham et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Second, increased neural synchrony, which has been linked to perceptual learning (Merzenich et al, 1999), can be demonstrated through changes in evoked potentials. Third, auditory evoked potentials have been shown to reflect perception in normal and impaired children (Neville et al, 1993;Ponton et al, 1996;Tonnquist-Uhlen, 1996;Jordan et al, 1997;Cunningham et al, 2000Cunningham et al, , 2001. Fourth, deficits in the encoding of speech signals in quiet have been demonstrated at the auditory brainstem level and in both quiet and noise at cortical levels in learning-impaired children (Kraus et al, 1996;Schulte-Koerne et al, 1998;Cunningham et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Neville et al, (1993) reported an atypical early negative ERP component in a subgroup of SLI children who demonstrated poor auditory temporal performance behaviourally. This component, time-locked to tones, was found to be reduced over the right hemisphere and delayed in latency, especially over temporal and parietal sites in the left hemisphere.…”
Section: Electrophysiological Studiesmentioning
confidence: 98%
“…One should always remember that brain and behaviour relationships are extremely complex and that behaviour is likely to rely on circuitry dispersed across the brain, rather than a distinct circumscribed area. As noted by Neville et al (1993), ''the developing organism displays a high degree of change both in different neural systems and in cognition, and thus provides an important opportunity to link variability in one trajectory to variability in the other.'' However, the careful use of increasingly fine-grained behavioural assessments in conjunction with stateof-the art brain imaging methods provides an unparalleled and increasing opportunity to obtain a clearer, more detailed picture of how neural development interacts with environmental influences across time to produce complex behaviours and individual variability in brain function.…”
Section: General Summarymentioning
confidence: 99%
“…However, results from several studies are consistent with the suggestion that attention to speech and/or auditory information may differ between SLI and TLD groups. Specifically, several studies have found later latency of N1 in, at least, a subset of Language Impaired (LI) children (Jirsa & Clontz, 1990;Neville, et al, 1993;Tonnquist-Uhlen, Borg, Persson & Spens, 1996), although this was not seen in other studies (e.g., Lincoln, et al, 1995;Marler, Champlin & Gillam, 2002). These differences in N1 latency could be due to reduced N1 negativity leading to the appearance of later N1 peak latency.…”
Section: Introductionmentioning
confidence: 96%